Immunosuppressive tumor microenvironment in pancreatic cancer: mechanisms and therapeutic targets - Pan, Da; Li, Xinyue; Qiao, Xiao; Wang, Qiqi (Frontiers in Immunology, 2025)
Pancreatic cancer is projected to become the second leading cause of cancer−related death by 2030. Conventional interventions including surgery, radiotherapy, and chemotherapy provide only modest survival benefits, underscoring an urgent need for more effective therapies. Although immunotherapy has revolutionized the management of several solid tumors, its clinical benefit in pancreatic cancer has so far been disappointing. Mounting evidence indicates that a highly immunosuppressive tumor microenvironment (TME), dominated by tumor−associated macrophages (TAMs), myeloid−derived suppressor cells (MDSCs), and regulatory T cells (Tregs), drives immune evasion, tumor progression, metastasis, and chemoresistance through complex cytokine and chemokine networks. This review summarizes current knowledge of these immunosuppressive mechanisms and provides emerging strategies aimed at re−educating or depleting these cellular constituents to enhance the efficacy of immunotherapy in pancreatic cancer.